Implementation of a Neural Network HEMT Model Into ADS - Thompson, Willie L. II; Miller, Eric V; White, Carl (Microwave Journal, 2001)
Neural network algorithms have been applied to various areas of engineering and computer science. A high electron-mobility transistor (HEMT) large-signal model has been implemented in the Advanced Design System (ADS) software package using a multilayered neural network. The neural network model was trained to the drain current, gate-source capacitance and gate-drain capacitance characteristics of an Angelov model previously developed. Training was done using the back-propagation algorithm, which achieved excellent results for the model. Linear and harmonic balance simulations were performed to compare the linear and power performance of the neural network model to the Angelov model, without any additional optimization after the initial training.